Unraveling the impact of financial literacy, financial technology adoption, and access to finance on small medium enterprises business performance and sustainability: a serial mediation model - Florentina Kurniasari; Nadiah Abd Hamid; Elissa Dwi Lestari (Cogent Business & Management)
This study investigates the impact of financial access, technology adoption, and literacy on the performance and sustainability of small and medium enterprises (SMEs) in Indonesia. Using data from 469 SMEs and employing a serial mediation model alongside importance-performance mapping analysis (IPMA), the research reveals that financial literacy enhances both loan availability and FinTech adoption. However, FinTech adoption has minimal direct impact on financial access. While the links between financial literacy, capital access, and business performance are moderate, financing access plays a crucial mediating role between FinTech adoption, financial literacy, and business outcomes. Financial literacy also serves as a key mediator in driving SME success when coupled with FinTech usage and funding access. To support long-term SME sustainability, policymakers should prioritize initiatives that strengthen financial literacy and access to capital. Although the study offers valuable insights, its scope is limited to Indonesian SMEs operating in traditional markets. Future research should broaden the framework to other regions and industries, and improve data reliability through triangulation methods.